Glocal Space in Spanglish Twitter Communication - Marina Yu. Semenova (Актуальные проблемы филологии и педагогической лингвистики, 2024)
The study of linguistic phenomena in media texts based on code-switching and code-mixing is a pressing issue, since their linguistic level reflects global processes of the multipolar world development. In particular, it results in post-standard modern languages and translingual idioms where language contact occurs. The article aims at determining the Spanglish language glocal space continuum at the lexical, semantic and grammatical levels. The material is based on tweets by the American satirist Rachel Figueroa, writing under the pseudonym Miguel Bloombito, for 2017–2022, selected using the continuous sampling method. A corpus of 1073 tweets was compiled and studied using morphological, syntactic, lexical and semantic analysis followed by statistical processing and mapping. The result is the identification of four modus categories that express meanings corresponding to glocal space. Methods for transmitting these meanings at the lexical, semantic and grammatical levels in Spanglish have been identified as well. Thus, it has been established that this translingual idiom boasts a full-fledged system of units and levels, which effectively conveys the meanings of all modus categories under consideration. In addition, data mapping allows us to conclude that Spanglish effectively performs communication tasks both within the same locale and between different locales. Finally, the study does not only empirically prove the validity of one of the hypotheses regarding the glocal space infinity, including its linguistic representation, but also demonstrates that modern language contact models correspond not to geography, but to the logistics of communication flows between various glocalized locales determined by geostrategic interests.